FRONTIERS IN BIOTECHNOLOGICAL INTERVENTIONS FOR RICE IMPROVEMENT - M. SHESHU MADHAV, B. VISHALAKSHI, B. UMAKANTH, B. SUNEEL, G. USHA and (The Journal of Research, PJTSAU, 2019)
Rice is the world’s most important cereal food crop and a staple food for more than half of the world’s population. The increase in food demand along with decline in the availability of arable land and water resources will be indeed difficult to meet the challenges only with the application of conventional plant breeding techniques and tools. Biotechnological tools as a viable solution to meet the rice production and productivity and helps to sustain the food security. The molecular techniques i.e., genomics-assisted selection, genetic engineering, functional genomics, genome editing and genome wide association studies has opened up novel opportunities for enhancing rice yields beyond the limits imposed by conventional breeding. These broad applications of biotechnology expected to contribute both directly and indirectly towards rice improvement. This review focuses on possibilities for the application of biotechnology tools in the genetic improvement of rice breeding.